Exercícios resistidos para idosas com obesidade sarcopênica: um ensaio clínico aleatorizado - Karina Simone de Souza Vasconcelos (2013)
During the aging, changes in body composition may lead to sarcopenic obesity (SO). This condition is characterized by excess of body weight and loss of muscle mass and strength, being more common among women. The SO is associated with functional disability, especially regarding mobility. The main objective of this study was to examine the effects of progressive resistance exercises for the functionality of elderly women with OS. The specific objectives were: 1) to develop and to test the feasibility of two resistance exercise programs for lower limbs - one as aquatic and one as land-based; 2) to determine the efficacy of a land-based resistance exercise program in three levels of functionality ; 3) to determine the effects of this exercise program in muscle performance of lower limbs and functional performance of locomotion activities. For the first specific objective, two exercise protocols were developed. The aquatic exercises were tested only in the pilot study. The effectiveness of land-based resistance training was tested in a randomized clinical trial with two parallel groups. Participants were aged 65-80 years, with BMI 30 kg/m2 and grip strength 21 Kgf. We measured socio-demographic, anthropometric and clinical characteristics of the sample. The level of physical activity was measured by the Human Activity Profile and the presence of depressive symptoms by the Geriatric Depression Scale - short version (GDS-10). The quality of life related to health was measured by the SF-36. The following functional tests were performed: Short Physical Performance Battery (SPPB), usual (10 m) and maximum gait speed (Shuttle Walking Test), usual speed for climbing up and down stairs and maximum speed for climbing stair. The performance of the knee flexors/extensors, hip flexors/extensors and abductors/adductors was measured using an isokinetic dynamometer. Allocation was randomized and concealed, in blocks. The exercise group (GES) participated in a 10-week resistance training for strength, power and endurance. The control group (GC) received phone calls weekly. Analysis was by intention to treat, with 14 volunteers in each group. For the second specific objective, the variables of handgrip strength and knee extensor strength, power and resistance were considered as muscle function. The activity level was characterized by the SPPB tests and the participation level by physical function domain of the SF-36. The number needed to treat (NNT) was calculated for improvement in gait speed. For the third specific objective, the strength and power of hip and knee muscles represented the muscle performance. The gait and stairs tests represented functional performance. In the first week, groups had similar characteristics. After intervention, the GES showed gains of 20% in muscle power of the knee extensors (p <0.001, r = -0.55) and 10% in grip strength (p <0.001, r = -0,66). There was no differencein the other levesl of functionality. The NNT for gait speed was 5 patients. The GES was significantly different regarding muscle performance (p = 0.05, r = -0.36). There was no difference in the functional performance (p = 0.74, t = -033). These results showed that resistance exercise programs can produce gains in muscle performance of elderly with SO. The effects of these exercises on functional activities remain unclear.